La determinación de las enfermedades raras o huérfanas a través de normativa propia garantiza el derecho a la salud. - Erreyes Becerra., Gina Gabriela (2021)
The present investigative work was carried out before a legal and modern problem, which happens to an important group of society, to people who suffer from rare or orphan diseases, so their physical, psychological well-being is sought, in a legal way and social, without discrimination and guaranteeing the rights that are recognized in the Constitution of the Republic of Ecuador. Conceptual analysis is carried out, which helps to understand the subject since several technical and medical terms may be unknown or unintelligible to the mass. Generally, people tend to confuse or ignore complex but significant and important terms, so the emphasis is placed on making them known, such as, mainly, the definition of rare diseases, which is disrupted by catastrophic diseases, which are very different, from its diagnosis and even more in its treatment. Likewise, a doctrinal study of the relevant points is carried out, contemplating the various theoretical conceptions about this type of disease. As they are not common diseases, and even though there are not many studies on the subject and that there is information in other languages, there are scholars who have managed to determine a series of conditions and ideas, which they try to communicate and emphasize so that people know, as it is, the relevance of this type of affections; how they can be supported in the various areas, psychological and social; or, in what concerns, how to strengthen legal support for people with a rare or orphan disease. 5 Consequently, a legal analysis is carried out, considering the rights and the norms by which they are regulated; as well as, a comparison, with the regulations of other countries, to be able to accept and understand this complex issue full of gaps. The country's Supreme Norm recognizes people with rare or orphan diseases as a vulnerable group, and, in the Organic Health Law through Reform Law No. 0, Official Registry 625, a chapter is included for these diseases, merging them with catastrophic diseases, which obviously due to their great differences does not provide any benefit to those who suffer from them, there are important and necessary issues, which are inconsistent or untreated, which prevents achieving a harmonious balance of the health of people with rare or orphan diseases. In various countries, through their laws, actions have been recognized and taken to provide various solutions to various problems of this vulnerable group. About this, research materials, methods, and techniques are used to fulfill the purpose of this study. Jointly, the field research is applied, though, first, the surveys, carried out on thirty legal and health professionals; second, the interviews carried out with five scholars on the subject; and, third, with the study of cases, real and patent, demonstrating the physical, legal, psychological and social difficulties suffered by their ailments. Next, a discussion is used that helps to verify the objectives, both general and specific, raised in this arduous investigation, as well as, the hypothesis of lack of proper regulations for people with rare or orphan diseases is contrasted. Therefore, conclusions and recommendations are provided, seeking the benefit of this group of vulnerable people. Due to the aforementioned, and emphasizing that law and medicine have been and are in constant relationship, as evidenced by both the country's legal system and the international system, the need for regulations is raised, to avoid the violation of the constitutional rights of people suffering from rare or orphan diseases, ensuring the right to health and life, which includes the evaluation of health technology, budget, financing, equipment, preventive diagnosis, adequate and effective treatment, application of medicine genomic-personalized, updating of the list of rare diseases existing in the country, as well as sanctions, and other legal situations.